Validation of scanning of neuro psychological the personality in university students - Sarria Joya, Cesar (2011)
Neuropsychological Scanning scale of Personality, prepared by C. Sarria, V. Llaja, P. García, M. Salazar, G. Salazar (2009) is a recent unpublished instrument designed to examine the structural components of the Personality System in university students, based on the theoretical model Informational (Ortiz, 1994, 1997, 2004a, 2004b). Through the study reported in this paper, we obtained evidence indicating that this instrument has content validity and construct and showed a high rate of reliability in terms of both: its internal consistency and factorial analysis on all items. Finally, qualitative analysis was performed neuropsychological so it can be used later in the neuropsychological examination of clinical samples, and educational.